Preeclampsia and Stroke: Risks during and after Pregnancy - Cheryl Bushnell; Monique Chireau (Stroke Research and Treatment)
Preeclampsia and stroke are significantly related, both pathologically and temporally (across the life span) in women. Cerebrovascular events can complicate preeclampsia, and can also manifest later in life. A history of preeclampsia is associated with long-term risk for hypertension, stroke, and heart disease. Cerebrovascular complications occur in only a small proportion of women with severe preeclampsia, but with high morbidity and mortality. Endothelial dysfunction and impaired cerebral autoregulation, and severe hypertension in the setting of preeclampsia are likely the cause of many strokes during pregnancy. The relationship between preeclampsia and stroke involves shared risk factors for both disorders, including chronic endothelial dysfunction and increased risk for long-term hypertension following preeclampsia (one of the major risk factors for stroke). This overlap provides insights into underlying pathophysiology and potential preventive strategies for both preeclampsia and stroke. For example, aspirin may prevent both disorders. The current review will describe the current data regarding these relationships and suggest future research to investigate remaining knowledge gaps. These are important topics for neurologists, who are likely to be involved with the care of severely ill preeclamptic patients with neurologic complications, as well as women at increased risk of stroke due to a history of preeclampsia.